Touchstone : student's book - McCarthy, Michael; McCarten, Jeanne; Sandiford, Helen (New York : Cambridge University Press, 2005)
Fácil y agradable de enseñar, Touchstone ofrece un nuevo enfoque para la enseñanza y el aprendizaje de Inglés.
Touchstone level 1A Scope and Sequence United 1: All about you United 2: In class United 3: Favorite people United 5: Everyday life United Free time Unit 6: Neighborhoods
Incluye -Student s book -Workbook - Video activity pages -Self-study audio CD/CD-ROM -Video on DVD
Keywords: INGLÉS -- GRAMÁTICA; ENGLISH; TEACHING OF ENGLISH; INGLÉS -- ENSEÑANZA; GRAMMAR